Ag / gamma-Al2O3 antibacterial material with layered structure and preparation method of Ag / gamma-Al2O3 antibacterial material

By preparing the AG/γ-Al2O3 antibacterial material of the layer-like structure, the existing nanoxoxicid material is inadequate in terms of uniformity and reused utilization, and achieves high-efficiency sterilization and long antibacterial effects on bacteria.

CN119325978APending Publication Date: 2025-01-21SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475209.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing nanoalumina materials have shortcomings in uniformity and reusability, which limits their widespread use in practical applications.

Method used

The preparation method of AG/γ-Al2O3 antibacterial materials with a layered structure is used to add Naalo2 and HNO3 solutions to the water, and then add the AGNO3 solution and anti-hemoglobin solution to prepare Out of AL2O3 load single atoms with atomic antibacterial materials with atomic atoms.

Benefits of technology

The material has excellent antibacterial activity and cycle use performance. The sterilization performance of Gram -negative E. coli and Gram -positive golden grape bacteria reached 100%and 99.98%, respectively. Effect.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an Ag / gamma-Al2O3 antibacterial material with a layered structure and a preparation method of the Ag / gamma-Al2O3 antibacterial material, and relates to the technical field of preparation of antibacterial nano materials. The preparation method comprises the following steps: firstly adding NaAlO2 into water, then adding an HNO3 solution, heating and stirring; the method comprises the following steps: firstly, adding an AgNO3 solution, and reacting for 10-60 minutes; injecting an ascorbic acid solution, and reacting for 20-40 minutes; heating to 40-100 DEG C, reacting for 4-5 hours, filtering, washing the precipitate, and drying in vacuum; and calcining the dried sample in inert gas flow for 1-5 hours to obtain the Ag / gamma-Al2O3 antibacterial material with the layered structure. The Al2O3-loaded monatomic antibacterial material containing atom-dispersed Ag atoms is successfully prepared by combining a nitric acid method and an oxidation-reduction method, and silver nanoparticles doped in aluminum oxide can continuously release silver ions, so that a long-term antibacterial effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of antibacterial nano materials, and in particular to a layered Ag / γ-Al2O3 antibacterial material and a preparation method thereof. Background Art

[0002] Overuse and abuse of antibiotics have led to an increase in drug-resistant bacteria, making many antibiotics gradually ineffective, posing a serious threat to human and animal health. In the past few decades, nanomedicine therapy has gradually emerged in the medical field as a non-antibiotic alternative. With its unique nano properties, it has brought new hope and opportunities for the treatment of diseases. Unlike traditional antibiotic therapy, nanomedicine can achieve targeted effects on diseased cells or tissues through precise design and preparation, thereby more effectively exerting therapeutic effects while reducing side effects on normal tissues. This innovative treatment method has shown great potential in many fields such as cancer treatment, infectious disease treatment, and chronic disease management. It can break through some limitations of traditional drug therapy, such as improving the bioavailability of drugs, enhancing the stability of drugs, and achieving controlled and sustained release of drugs. Nanomaterials have great potential in the field of antimicrobial applications. Compared with traditional materials, nanoparticle materials have significant advantages due to their small size, large specific surface area, and strong adsorption and catalytic capabilities. Among various inorganic materials, Ag NPs and Al2O3 are considered to be effective antimicrobial agents. Nanosilver has become a promising nano-fungicide due to its effectiveness and minimal toxicity and side effects. Nanosilver has a high adsorption capacity for microorganisms and then produces Ag + and reactive oxygen species (ROS), which are responsible for the rupture of the microbial shell. Activated alumina (γ-Al2O3) is a common industrial catalyst with a relatively uniform mesoporous structure and high surface area, as well as excellent thermal stability. In addition, Al2O3 nanoparticles are ideal for drug carriers and have a wide range of applications in thermal sensors and catalyst carriers. Al2O3 nanoparticles also have the advantages of low toxicity, low cost, and a variety of surface modifications.

[0003] Although there have been many studies on the antibacterial properties of nano-alumina, it is still a major challenge to improve the biocatalytic active sites of nanomaterials due to the shortcomings of traditional nanomaterials in terms of uniformity and reusability. These problems limit the widespread use of nano-alumina in practical applications. Therefore, developing new nanomaterials or improving the structure and properties of existing materials to enhance their antibacterial effects and reusability has become an important direction of current research. This not only helps to improve antibacterial efficiency, but also reduces costs and reduces environmental impact. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention aims to provide a layered Ag / γ-Al2O3 antibacterial material and a preparation method thereof.

[0005] One of the purposes of the present invention is to provide a method for preparing a layered Ag / γ-Al2O3 antibacterial material, the preparation method comprising: S1 first add NaAlO2 and then HNO3 solution to water, heat and stir; S2 first adds AgNO3 solution and reacts for 10 to 60 minutes; then injects ascorbic acid solution and reacts for 20 to 40 minutes; S3 is heated to 40-100°C, reacted for 4-5 hours, filtered, and the precipitate is washed and vacuum dried; S4 calcined the dried sample in an inert gas flow for 1 to 5 hours to obtain a layered structured Ag / γ-Al2O3 antibacterial material.

[0006] Preferably, the molar ratio of AgNO3 to NaAlO2 is 0.0025~0.015:1.

[0007] Preferably, the molar ratio of ascorbic acid to AgNO3 in step S2 is 0.5-1.5:1.

[0008] Preferably, the pH of the reaction system in steps S1 and S2 is 5-9.

[0009] Preferably, the reaction temperature of step S1 is 40-80°C, and the reaction temperature of step S2 is 40-50°C.

[0010] Preferably, the reaction temperature of step S3 is 40-100°C.

[0011] Preferably, the reaction time of step S1 is 10 to 40 min.

[0012] Preferably, the vacuum drying temperature in step S3 is 50-79° C., and the drying time is 11-13 hours.

[0013] Preferably, the calcination temperature in step S4 is 300-700°C, and the inert gas flow rate is 40 mL min -1 .

[0014] The second object of the present invention is to provide a layered structured Ag / γ-Al2O3 antibacterial material.

[0015] The beneficial effects of the present invention include: The present invention successfully prepares an Al2O3-loaded single-atom antibacterial material containing atomically dispersed Ag atoms by combining the nitric acid method with the redox method. This method maximizes the atomic utilization and density of active sites. The uniform structure of the material gives it excellent antibacterial activity and recycling performance. The prepared antibacterial material has excellent bactericidal properties against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus, which are 100% and 99.98% respectively. Silver nanoparticles doped in alumina can continuously release silver ions, thereby achieving a long-lasting antibacterial effect. DETAILED DESCRIPTION

[0016] According to the first aspect of the present invention, a method for preparing a layered Ag / γ-Al2O3 antibacterial material is provided, the preparation method comprising: S1 first add NaAlO2 and then HNO3 solution to water, heat and stir; S2 first adds AgNO3 solution and reacts for 10 to 60 minutes; then injects ascorbic acid solution and reacts for 20 to 40 minutes; S3 is heated to 40-100°C, reacted for 4-5 hours, filtered, and the precipitate is washed and vacuum dried; S4 calcining the dried sample in an inert gas flow for 1 to 5 hours to obtain a layered Ag / γ-Al2O3 antibacterial material. In the present invention, the solvents of the sodium aluminate solution and the nitric acid solution are both water, preferably pure water.

[0017] In the present invention, the atomically dispersed silver atoms have extremely high specific surface area and reactivity, and can effectively release silver ions, which have significant antibacterial effects and can inhibit the growth and reproduction of bacteria. Silver ions interfere with the metabolic process of cells by binding to bacterial cell membranes, leading to cell death. In addition, silver ions can also react with sulfur and phosphorus groups in bacteria to further enhance their antibacterial ability.

[0018] The Al2O3 in the material, as a carrier, not only provides good structural stability and mechanical strength, but also can effectively fix silver atoms to prevent them from falling off or losing during use. The formation of a layered structure allows silver atoms to be evenly distributed on the surface of Al2O3, improving the recyclability of the material. After proper cleaning and regeneration, the antibacterial properties of the material can remain relatively stable and suitable for multiple uses.

[0019] In a preferred embodiment of the present invention, the molar ratio of AgNO3 to NaAlO2 is 0.0025~0.015:1.

[0020] In the present invention, the molar ratio of AgNO3 and NaAlO2 is, for example, 0.0025:1, 0.005:1, 0.0075:1, 0.010:1, 0.0125:1 or 0.015:1.

[0021] In a preferred embodiment of the present invention, the molar ratio of ascorbic acid to AgNO3 in step S2 is 0.5-1.5:1.

[0022] In the present invention, the molar ratio of ascorbic acid to AgNO3 in step S2 is, for example, 0.5:1, 1:1 or 1.5:1.

[0023] In a preferred embodiment of the present invention, the pH of the reaction system in steps S1 and S2 is 5-9.

[0024] In the present invention, the pH of the reaction system in step S2 is, for example, 5, 6, 7, 8 or 9.

[0025] In a preferred embodiment of the present invention, the reaction temperature of step S1 is 40-80°C, and the reaction temperature of step S2 is 40-50°C.

[0026] In the present invention, the reaction temperature of step S1 is, for example, 40°C, 50°C, 60°C, 70°C or 80°C; the reaction temperature of step S2 is, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C.

[0027] In a preferred embodiment of the present invention, the reaction temperature of step S3 is 40-100°C.

[0028] In the present invention, the reaction temperature of step S3 is, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C.

[0029] In a preferred embodiment of the present invention, the reaction time of step S1 is 10 to 40 min.

[0030] In the present invention, the reaction time of step S1 is, for example, 10 min, 20 min, 30 min or 40 min.

[0031] In a preferred embodiment of the present invention, the vacuum drying temperature in step S3 is 50-79° C., and the drying time is 11-13 hours.

[0032] In the present invention, the vacuum drying temperature in step S3 is, for example, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 79°C; the drying time is, for example, 11 hours, 11.5 hours, 12 hours, 12.5 hours or 13 hours.

[0033] In a preferred embodiment of the present invention, the calcination temperature in step S4 is 300-700°C, and the inert gas flow rate is 40 mL min -1 .

[0034] In the present invention, the calcination temperature in step S4 is, for example, 300°C, 400°C, 500°C, 600°C or 700°C.

[0035] In the present invention, the preparation method of the layered Ag / γ-Al2O3 antibacterial material is specifically as follows: S1: First add NaAlO2 in water, and when the temperature rises to 40-80℃, add 38% nitric acid and 16.17ml pure water solution, the pH of the reaction system is 5-9, and heat and stir for 10-40 min; S2 first adds AgNO3 solution and reacts for 10-60 minutes; then injects ascorbic acid solution while maintaining the temperature at 40-50°C and reacts for 20-40 minutes. The molar ratio of AgNO3 to NaAlO2 is 0.0025-0.015:1, and the molar ratio of ascorbic acid to AgNO3 is 0.5-1.5:1; S3 is heated to 40-100°C, reacted for 4-5 hours, filtered, and the precipitate is washed three times with deionized water and anhydrous ethanol, and then dried in a vacuum chamber at 50-79°C for 11-13 hours; S4 dried the sample at a flow rate of 40 mL min -1 The Ag / γ-Al2O3 antibacterial material with a layered structure is obtained by calcining in an inert gas flow for 1 to 5 hours at a calcination temperature of 300 to 700°C.

[0036] According to the second aspect of the present invention, a high-layered Ag / γ-Al2O3 antibacterial material is provided.

[0037] Example 1 S1: First add 16.4g of NaAlO2 to 164mL of water, then add 14.38mL of 38% nitric acid and 15.97ml of pure water when the temperature rises to 40℃, and heat and stir to react for 20 minutes; Add 0.5 mL of S2 to a concentration of 1 mol L -1 AgNO3 solution was reacted for 30 minutes; the temperature was maintained at 40°C and 0.5 mL of 1 mol L -1 Ascorbic acid solution was added and reacted for 30 minutes. At this time, the pH of the reaction system was 7.38. The pH of the reaction system should be determined by the amount of nitric acid added and the temperature. S3 maintained at 40°C, reacted for 4 hours, and then filtered. The precipitate was washed with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum chamber at 60°C for 12 hours to obtain Ag-AlOOH. S4 dried the sample at a flow rate of 40 mL min -1 The material was calcined at 500°C for 3 hours in an argon gas flow to obtain a layered Ag / γ-Al2O3 antibacterial material with a specific surface area of ​​196.33 and an antibacterial effect of 95.14% and 93.56% against Escherichia coli and Staphylococcus aureus.

[0038] Example 2 S1: First add 16.4g of NaAlO2 to 164mL of water, then add 15.25mL of 38% nitric acid and 15.10ml of pure water when the temperature rises to 40℃, and heat and stir to react for 20 minutes; Add 0.5 mL of S2 to a concentration of 1 mol L -1 AgNO3 solution was reacted for 30 minutes; the temperature was maintained at 40°C, and 0.5 mL of 1 mol L -1 Ascorbic acid solution was added and reacted for 30 minutes, at which time the pH of the reaction system was 5.67; S3 was heated to 40°C, reacted for 4 hours, and then filtered. The precipitate was washed with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum chamber at 60°C for 12 hours to obtain Ag-AlOOH. S4 dried the sample at a flow rate of 40 mL min -1 The material was calcined at 300-700 °C for 3 hours in an argon gas flow to obtain a layered Ag / γ-Al2O3 antibacterial material with a specific surface area of ​​136.26 and an antibacterial effect of 89.19% and 88.36% against Escherichia coli and Staphylococcus aureus.

[0039] Example 3 S1: First add 16.4g of NaAlO2 to 164mL of water, then add 15.25mL of 38% nitric acid and 15.10ml of pure water when the temperature rises to 40℃, and heat and stir to react for 20 minutes; Add 0.5 mL of S2 to a concentration of 1 mol L -1 AgNO3 solution was reacted for 30 minutes; the temperature was maintained at 40°C, and 0.5 mL of 1 mol L -1 Ascorbic acid solution was added and reacted for 30 minutes, at which time the pH of the reaction system was 5.67; S3 was heated to 60°C, reacted for 4 hours, and then filtered. The precipitate was washed with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum chamber at 60°C for 12 hours to obtain Ag-AlOOH. S4 dried the sample at a flow rate of 40 mL min -1 The material was calcined at 300-700 °C for 3 hours in an argon gas flow to obtain a layered Ag / γ-Al2O3 antibacterial material with a specific surface area of ​​145.29 and an antibacterial effect of 91.22% and 89.33% against Escherichia coli and Staphylococcus aureus.

[0040] Example 4 S1: First add 16.4g of NaAlO2 to 164mL of water, then add 15.25mL of 38% nitric acid and 15.10ml of pure water when the temperature rises to 40℃, and heat and stir to react for 20 minutes; Add 0.5 mL of S2 to a concentration of 1 mol L -1 AgNO3 solution was reacted for 30 minutes; the temperature was maintained at 40°C, and 0.5 mL of 1 mol L -1 Ascorbic acid solution was added and reacted for 30 minutes, at which time the pH of the reaction system was 5.67; S3 was heated to 80°C, reacted for 4 hours, and then filtered. The precipitate was washed with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum chamber at 60°C for 12 hours to obtain Ag-AlOOH. S4 dried the sample at a flow rate of 40 mL min -1 The material was calcined at 300-700 °C for 3 hours in an argon gas flow to obtain a layered Ag / γ-Al2O3 antibacterial material with a specific surface area of ​​163.45 and an antibacterial effect of 93.21% and 91% against Escherichia coli and Staphylococcus aureus.

[0041] Example 5 S1: First add 16.4g of NaAlO2 to 164mL of water, then add 15.25mL of 38% nitric acid and 15.10ml of pure water when the temperature rises to 40℃, and heat and stir to react for 20 minutes; Add 0.5 mL of S2 to a concentration of 1 mol L -1 AgNO3 solution was reacted for 30 minutes; the temperature was raised to 50°C, and 0.5 mL of 1 mol L -1 Ascorbic acid solution was added and reacted for 30 minutes, at which time the pH of the reaction system was 5.67; S3 was heated to 100°C, reacted for 4 hours, and then filtered. The precipitate was washed with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum chamber at 60°C for 12 hours to obtain Ag-AlOOH. S4 dried the sample at a flow rate of 40 mL min -1The material was calcined at 300-700 °C for 3 hours in an argon gas flow to obtain a layered Ag / γ-Al2O3 antibacterial material with a specific surface area of ​​136.26 and an antibacterial effect of 89.19% and 88.36% against Escherichia coli and Staphylococcus aureus.

[0042] Example 6 S1: First add 16.4g of NaAlO2 to 164mL of water, then add 15.25mL of 38% nitric acid and 15.10ml of pure water when the temperature rises to 60℃, and heat and stir to react for 20 minutes; Add 0.5 mL of S2 to a concentration of 1 mol L -1 AgNO3 solution was reacted for 30 minutes; the temperature was lowered to 40°C, and 0.5 mL of 1 mol L -1 Ascorbic acid solution was added and reacted for 30 minutes, at which time the pH of the reaction system was 5.67; S3 was heated to 80°C, reacted for 4 hours, and then filtered. The precipitate was washed with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum chamber at 60°C for 12 hours to obtain Ag-AlOOH. S4 dried the sample at a flow rate of 40 mL min -1 The material was calcined at 300-700 °C for 3 hours in an argon gas flow to obtain a layered Ag / γ-Al2O3 antibacterial material with a specific surface area of ​​106.28 and an antibacterial effect of 85.66% and 83.26% against Escherichia coli and Staphylococcus aureus.

[0043] Example 7 S1: First add 16.4g of NaAlO2 to 164mL of water, then add 15.25mL of 38% nitric acid and 15.10ml of pure water when the temperature rises to 80℃, and heat and stir to react for 20 minutes; Add 0.5 mL of S2 to a concentration of 1 mol L -1 AgNO3 solution was reacted for 30 minutes; the temperature was lowered to 40°C, and 0.5 mL of 1 mol L -1 Ascorbic acid solution was added and reacted for 30 minutes, at which time the pH of the reaction system was 5.67; S3 was heated to 80°C, reacted for 4 hours, and then filtered. The precipitate was washed with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum chamber at 60°C for 12 hours to obtain Ag-AlOOH. S4 dried the sample at a flow rate of 40 mL min -1The material was calcined at 300-700 °C for 3 hours in an argon gas flow to obtain a layered Ag / γ-Al2O3 antibacterial material with a specific surface area of ​​157.27 and an antibacterial effect of 92.15% and 90.77% against Escherichia coli and Staphylococcus aureus.

[0044] Example 8 S1: First add 16.4g of NaAlO2 to 164mL of water, then add 14.28mL of 38% nitric acid and 16.07ml of pure water when the temperature rises to 80℃, and heat and stir to react for 20 minutes; Add 0.5 mL of S2 to a concentration of 1 mol L -1 AgNO3 solution was reacted for 30 minutes; the temperature was lowered to 40°C, and 0.5 mL of 1 mol L -1 Ascorbic acid solution was added and reacted for 30 minutes, at which time the pH of the reaction system was 7.86; S3 was heated to 80°C, reacted for 4 hours, and then filtered. The precipitate was washed with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum chamber at 60°C for 12 hours to obtain Ag-AlOOH. S4 dried the sample at a flow rate of 40 mL min -1 The material was calcined at 300-700 °C for 3 hours in an argon gas flow to obtain a layered Ag / γ-Al2O3 antibacterial material with a specific surface area of ​​224.23 and an antibacterial effect of 98.22% and 97.63% against Escherichia coli and Staphylococcus aureus.

[0045] Example 9 S1: First add 16.4g of NaAlO2 to 164mL of water, then add 14.18mL of 38% nitric acid and 16.17ml of nitric acid when the temperature rises to 50℃, and heat and stir to react for 20 minutes; Add 0.5 mL of S2 to a concentration of 1 mol L -1 AgNO3 solution was reacted for 30 minutes; then 0.5 mL of 1 mol L -1 Ascorbic acid solution was added and reacted for 30 minutes, at which time the pH of the reaction system was 8.98; S3 was heated to 80°C, reacted for 4 hours, and then filtered. The precipitate was washed with deionized water and anhydrous ethanol for 3 times and then dried in a vacuum chamber at 60°C for 12 hours to obtain Ag-AlOOH. S4 dried the sample at a flow rate of 40 mL min -1 The material was calcined at 300-700 °C for 3 hours in an argon gas flow to obtain a layered Ag / γ-Al2O3 antibacterial material with a specific surface area of ​​266. The antibacterial effects against Escherichia coli and Staphylococcus aureus were 100% and 99.98% respectively.

Claims

1. A method for preparing a layered Ag / γ-Al2O3 antibacterial material, characterized in that: include: S1 first add NaAlO2 and then HNO3 solution to water, heat and stir; S2 adds AgNO3 solution and reacts for 10 to 60 minutes; then injects ascorbic acid solution and reacts for 20 to 40 minutes; S3 is heated to 40-100°C, reacted for 4-5 hours, filtered, and the precipitate is washed and vacuum dried; S4 calcined the dried sample in an inert gas flow for 1 to 5 hours to obtain a layered structured Ag / γ-Al2O3 antibacterial material.

2. The method for preparing the layered Ag / γ-Al2O3 antibacterial material according to claim 1, characterized in that: The molar ratio of AgNO3 and NaAlO2 is 0.0025~0.015:

1.

3. The method for preparing the layered Ag / γ-Al2O3 antibacterial material according to claim 1, characterized in that: The molar ratio of ascorbic acid to AgNO3 in step S2 is 0.5-1.5:

1.

4. The method for preparing the layered Ag / γ-Al2O3 antibacterial material according to claim 1, characterized in that: The pH of the reaction system in steps S1 and S2 is 5-9.

5. The method for preparing the Ag / γ-Al2O3 antibacterial material with a layered structure as claimed in claim 1, characterized in that: The reaction temperature of step S1 is 40-80°C, and the reaction temperature of step S2 is 40-50°C.

6. The method for preparing the Ag / γ-Al2O3 antibacterial material with a layered structure as claimed in claim 1, characterized in that: The reaction temperature of step S3 is 40-100°C.

7. The method for preparing the Ag / γ-Al2O3 antibacterial material with a layered structure as claimed in claim 1, characterized in that: The reaction time of step S1 is 10 to 40 min.

8. The method for preparing the Ag / γ-Al2O3 antibacterial material with a layered structure as claimed in claim 1, characterized in that: The vacuum drying temperature in step S3 is 50-79° C., and the drying time is 11-13 hours.

9. The method for preparing the Ag / γ-Al2O3 antibacterial material with a layered structure as claimed in claim 1, characterized in that: Step S4: calcination temperature is 300-700°C, inert gas flow rate is 40 mL min -1 .

10. An Ag / γ-Al2O3 antibacterial material with a layered structure prepared by the preparation method according to claims 1 to 9.